RELATIONSHIP BETWEEN ANTHROPOMETRIC PARAMETERS AND VERTICAL JUMP PERFORMANCE IN CADET VOLLEYBALL SELECTION - Stanković, Daliborka (Sport - nauka i praksa, 2026)
Volleyball is a team sport played by two teams on a court divided by a net. It is an intense sport that combines vertical and horizontal movements, involving anaerobic energy systems with short recovery periods. The anthropometric characteristics of athletes are a significant prerequisite for successful engagement in a specific sport, influencing athletic performance and being essential for achieving elite sports skills. The aim of this study is to determine the relationship between anthropometric parameters and vertical jump performance in female volleyball cadets. A research study was conducted to assess motor abilities and physical characteristics of 40 female volleyball players. Anthropometric parameters, including body height, body mass, body fat percentage, muscle mass percentage, and body mass index, as well as arm span, were measured using appropriate instruments. Motor abilities were evaluated through a vertical jump test using the OptoJump system. Pearson correlation coefficients revealed significant positive correlations between countermovement jump (CMJ) and muscle mass percentage (r=0.588, p<0.001), arm span (r=0.515, p<0.001), body height (r=0.502, p=0.001), and body mass (r=0.342, p=0.031). Muscle mass percentage was identified as a statistically significant predictor (B=1.488, p=0.004), while arm span also showed a significant positive association with CMJ (B=0.095, p=0.002). Conversely, body mass (B=0.233, p=0.146) and body height (B=-0.238, p=0.447) were not statistically significant predictors in this model. The multiple regression analysis results indicate the statistical significance of the model (F=6.667, p<0.001), with a multiple correlation coefficient R=0.660. The findings of this study emphasize the need for a multidimensional approach in training processes, which should include not only physical conditioning but also biomechanical and technical factors.